Low Power Design Techniques And Its Implementation On Direct Memory Access (DMA) - Shabagran, Gandi (2012)

(untitled)
As the number of transistors in a SoC has been increasing rapidly, the integration complexity has increased as well. Besides complexity, IC designers also faced some other challenges including maintaining the power, performance and area of an IC. Bilangan transistor dalam SoC yang meningkat secara mendadak telah menyebabkan kerumitan integrasi turut meningkat pada masa yang sama. Selain kerumitan integrasi, pereka IC juga menghadapi beberapa cabaran termasuk untuk mengekalkan kuasa, prestasi dan keluasan IC.